2014
DOI: 10.1007/s11552-014-9673-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Metacarpal Fracture Fixation: Application of a 90° Internal Fixation Model

Abstract: Purpose Complications in metacarpal fracture treatment increase in proportion to the severity of the initial injury and the invasiveness of the surgical fixation technique. This manuscript evaluates the feasibility of minimizing internal fixation construct size and soft tissue dissection, while preserving the advantages of stable internal fixation in a biomechanical model. We hypothesized that comparable construct stability could be achieved with mini-plates in an orthogonal (90/90) configuration compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…(2019) reported higher peak loads between 119 N and 212 N for intramedullary screw fixation of midshaft transverse osteotomies in a 3-point bending test protocol. In our model, we used cantilever bending instead of 3-point bending because this technique may mimic the in vivo configuration after metacarpal fracture fixation most accurately (Nicklin et al., 2008; Watt et al., 2015). However, due to the fixation of the specimen at its base, cantilever bending may be associated with system failure rather than construct failure (Watt et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) reported higher peak loads between 119 N and 212 N for intramedullary screw fixation of midshaft transverse osteotomies in a 3-point bending test protocol. In our model, we used cantilever bending instead of 3-point bending because this technique may mimic the in vivo configuration after metacarpal fracture fixation most accurately (Nicklin et al., 2008; Watt et al., 2015). However, due to the fixation of the specimen at its base, cantilever bending may be associated with system failure rather than construct failure (Watt et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, 3/24 specimens fractured at the base before construct failure. Failure at the bone/PMMA interface is not unusual for cantilever bending and does not depend on the type of specimen (Sohn et al., 2008; Watt et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…5,17,18,21 In addition, biomechanical studies have found dorsal plating, KW pinning, and intramedullary nailing to have reasonable stability across a metacarpal fracture site with dorsal plating being the most stable. 2,16,32 While clinically successful and biomechanically sound, the utility of these strategies is limited by a complication rate of up to 36%. 5,17,18,21 These complications include infection, 3,18 tendon injury, 21 malunion, 22 nonunion, 22 avascular necrosis, 15 stiffness, 17,21 and tendon adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…As a practical matter, no in vitro biomechanical tests can authentically reflect physiological loadings. In addition to the modified three-point bending test [ 15 , 30 , 31 ], cantilever bending tests [ 32 , 35 ], three-point bending tests [ 36 ], four-point bending tests [ 19 , 37 ], and torsional tests [ 32 , 38 ] have been adopted in previous studies. In this study, the cantilever bending test was not used because our pilot experiment revealed that the proximal end of the metacarpal bone was removed from the custom fixture with bone cement clamps during the cantilever bending loading.…”
Section: Discussionmentioning
confidence: 99%